Companion animals in society - Zawistowski, Stephen (Thomson/Delmar Learning, 2008)
Since companion animals are a significant part of American society, a substantial body of research has been developed to demonstrate how they play a significant role impacting the physical and psychological health of people of all ages. Animal companions also help to drive an economic engine estimated at near forty billion dollars per year for food, toys, veterinary care and other support services and products. Companion Animals in Society combines the current available knowledge on companion animal husbandry with an introduction to these issues and how society is currently coping with them in order to provide the most useful resource in the market today